Removal of Iron(II) Using Intercalated Ca/Al Layered Double Hydroxides with [α-SiW12O40]4- - Tarmizi Taher; Mikha Meilinda Christina; Muhammad Said; Nurlisa Hidayati; Ferlinahayati Ferlinahayati; Aldes Lesbani (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2019)
Ca/Al layered double hydroxide (LDH) was successfully synthesized by co-precipitation method at pH 11 under room temperature condition then followed by calcination at 800 oC. The synthesized Ca/Al LDH was further intercalated with Keggin ion [α-SiW12O40]4- in order to prepare the intercalated form of Ca/Al LDH. The synthesized materials were characterized by X-ray diffraction (XRD) and Fourier transform infrared (FT-IR) and used as an adsorbent for iron(II) removal from the aqueous medium. The adsorption performance was investigated by studying the kinetics and thermodynamic properties of the adsorption process. The results showed that pristine Ca/Al LDH exhibited diffraction peak at 2θ about 20o which corresponds to the layer structure of the LDH material. For the intercalated Ca/Al LDH, the diffraction observed at 2θ around 30-40o indicated that the [α-SiW12O40]4- was successfully intercalated into the interlayer space of Ca/Al LDH. Furthermore, the intercalated Ca/Al LDH showed higher adsorption capacity toward iron(II) than the pristine form of Ca/Al LDH.